Detection of Insect-Specific Flaviviruses in Mosquitoes (Diptera: Culicidae) in Northeastern Regions of South Africa - Milehna M. Guarido (MDPI AG, 2021)
Mosquitoes in the Aedes and Culex genera are considered the main vectors of pathogenic flaviviruses worldwide. Entomological surveillance using universal flavivirus sets of primers in mosquitoes can detect not only pathogenic viruses but also insect-specific ones. It is hypothesized that insect-specific flaviviruses, which naturally infect these mosquitoes, may influence their vector competence for zoonotic arboviruses. Here, entomological surveillance was performed between January 2014 and May 2018 in five different provinces in the northeastern parts of South Africa, with the aim of identifying circulating flaviviruses. Mosquitoes were sampled using different carbon dioxide trap types. Overall, 64,603 adult mosquitoes were collected, which were screened by RT-PCR and sequencing. In total, 17 pools were found positive for insect-specific Flaviviruses in the mosquito genera Aedes (12/17, 70.59%) and Anopheles (5/17, 29.41%). No insect-specific viruses were detected in Culex species. Cell-fusing agent viruses were detected in Aedes aegypti and Aedes caballus. A range of anopheline mosquitoes, including Anopheles coustani, An. squamosus and An. maculipalpis, were positive for Culex flavivirus-like and Anopheles flaviviruses. These results confirm the presence of insect-specific flaviviruses in mosquito populations in South Africa, expands their geographical range and indicates potential mosquito species as vector species.